Hubungan Kebiasaan Merokok Orang Tua dengan Kejadian Pneumonia Pada Balita - Putu Susy Natha Astini; Ronny Andrian Gupta; Ni Luh Putu Yunianti Suntari; I Dewa Ayu Ketut Surinati (Jurnal Gema Keperawatan, 2020)
Pneumonia is a disease caused by bacteria pneumococcus, staphylococcus, streptococcus, and viruses. The causes of pneumonia are divided into intrinsic factors and extrinsic factors. The type of research used in this study was non-experimental research with a type of correlational research and cross sectional approach using non probability sampling with purposive sampling. The number of samples is 56 toddlers. This research was conducted in April to May 2019. Data collection using a questionnaire. The results showed that parents with the most smoking habits aged 30 years, with male sex (80.4%), work for self-employed or service traders (35.8%), high school education or SMK (50%), current smoking status (62.5%), no smoking (37.5%), duration of smoking 10 years (44.6%), and active smokers (62.5%). Hypothesis testing uses the chi square test and multiple logistic regression with p values of 0.024 each and the most related variable is the type of smoker with an OR value of 19.00.